Assessing falls risk in older adult mental health patients: A Western Australian review - Heslop, Karen; Wynaden, Dianne; Bramanis, K.; Connolly, C.; Gee, T.; Grifiths, R.; Al Omari, Omar (Wiley-Blackwell Publishing Asia, 2012)
Falls are a common and costly complication of hospitalization, particularly in older adult populations. This paper presents the results of a review of 139 falls at two older adult mental health services in Western Australia, Australia, over a 12-month period. Data were collected from the hospital incident report management system and from case file reviews of patients who sustained a fall during hospitalization. The results demonstrated that the use of different risk assessment and falls management tools led to variations in practice, policies, and management strategies. The review identified mental health-specific falls risk factors that place older people with a mental illness at risk when admitted to the acute mental health setting. With the expansion of community mental healthcare, many older people with a mental illness are now cared for in a variety of health-care settings. In assessing falls risk and implementing falls-prevention strategies, it is important for clinicians to recognize this group as an ambulant population with a fluctuating course of illness. They have related risks that require specialized falls assessment and management.